2014
DOI: 10.7863/ultra.33.4.641
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Probability of Malignancy With BI‐RADS Sonographic Features

Abstract: A naïve Bayes model provides a systematic approach for combining sonographic features and other patient characteristics for assessing the probability of malignancy to differentiate malignant and benign breast masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Other previous studies have shown that the US features that most likely predict a malignant diagnosis are irregular shapes, nonparallel orientations, and no circumscribed margin (22)(23)(24)(25). Our results were consistent with these findings, suggesting that other US features, such as internal echo, posterior features, calcification, and vascularity, cannot be used as significant predictors for malignancy (24,25). The US is a useful imaging modality to evaluate axillary nodes using morphological criteria, such as cortical thickening, hilar effacement, and nonhilar cortical blood flow.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other previous studies have shown that the US features that most likely predict a malignant diagnosis are irregular shapes, nonparallel orientations, and no circumscribed margin (22)(23)(24)(25). Our results were consistent with these findings, suggesting that other US features, such as internal echo, posterior features, calcification, and vascularity, cannot be used as significant predictors for malignancy (24,25). The US is a useful imaging modality to evaluate axillary nodes using morphological criteria, such as cortical thickening, hilar effacement, and nonhilar cortical blood flow.…”
Section: Discussionmentioning
confidence: 97%
“…Benndorf et al reported that breast cancer's family history was an independent risk factor (odds ratio: 5.53) in the setting of an MG BI-RADS 3 assessment (21). Other previous studies have shown that the US features that most likely predict a malignant diagnosis are irregular shapes, nonparallel orientations, and no circumscribed margin (22)(23)(24)(25). Our results were consistent with these findings, suggesting that other US features, such as internal echo, posterior features, calcification, and vascularity, cannot be used as significant predictors for malignancy (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…There continues to be a need for further innovations to improve confidence and reliability of breast imaging. In this context, several studies have proposed the use of computer algorithms and machine learning methods to improve the diagnostic value of breast ultrasound [ 2 ]-[ 7 ]. These computer based systems can serve as a second reader to decrease false positive rates of breast images [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These computer based systems can serve as a second reader to decrease false positive rates of breast images [ 2 ]. In our earlier study, we introduced an approach that combines individual sonographic features quantitatively by machine learning to determine the probability of malignancy of solid breast masses [ 7 ]. The results show that the Bayesian method of weighting provides a systematic approach for combining ultrasound BI-RADS features yielding a high level of diagnostic performance, with an A z of approximately 0.884.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation